Chapter 1: AIDS and Homophobia/Heterosexism - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 1995)
Homophobia and heterosexism are complementary social processes that shaped the social construction and the public health response to AIDS. Both concepts view gay and lesbian oppression from different vantage points. Homophobia is a weapon of sexism and is manifested in fear and hatred. Heterosexism is an ideological system that denigrates non-heterosexual behavior. Both processes are well served by the social institutions of family, religion, law, and the ideologies of sexuality and gender. The consequences have been societal and personal: inadequate HIV medical and social services; lack of a national AIDS policy; widespread discrimination and prejudice against gay men, lesbians, and persons living with AIDS; stress, violence, and suicide; substance abuse; and HIV risk behavior and relapse. Mental health and social services, social supports, education and prevention programs, community development, and social action to broaden civil rights and to challenge institutional oppression are required to counter the ravages of hate and discrimination. © 1995 Taylor & Francis Group, LLC.
5 citations (Crossref) [2023-10-31] Citation Key Alias: pop00186 tex.type: [object Object]
Keywords: dept.swk